2020
DOI: 10.48550/arxiv.2008.02215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Time Leap Challenge for SAT Solving

Abstract: We compare the impact of hardware advancement and algorithm advancement for SATsolving over the last two decades. In particular, we compare 20-year-old SAT-solvers on new computer hardware with modern SAT-solvers on 20-year-old hardware. Our findings show that the progress on the algorithmic side has at least as much impact as the progress on the hardware side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Grace (2013) found that hardware improvements account for half of the progress for several problems in the vicinity of AI research like computer chess, computer go and physics simulations. More recently, Fichte et al (2020) observed the same for progress in SAT solvers. In the realm of deep learning, Hernandez & Brown (2020) investigated improvements in algorithmic efficiency by holding final performance on various benchmarks constant and analyzing how the number of FLOPS needed to reach that level changed over time.…”
Section: Algorithmic Progress and Increased Efficiencymentioning
confidence: 60%
“…Grace (2013) found that hardware improvements account for half of the progress for several problems in the vicinity of AI research like computer chess, computer go and physics simulations. More recently, Fichte et al (2020) observed the same for progress in SAT solvers. In the realm of deep learning, Hernandez & Brown (2020) investigated improvements in algorithmic efficiency by holding final performance on various benchmarks constant and analyzing how the number of FLOPS needed to reach that level changed over time.…”
Section: Algorithmic Progress and Increased Efficiencymentioning
confidence: 60%